Reviving contemporary urban design: case of historic city Sultanpur LodhI, Punjab, India - Sharma, Vikas Chand (Journal of Architecture and Urbanism, 2018)
Cities have a long and varied urban history, but cities in developing countries have had a relatively brief experience with the modern city. What are the current urban ideas of Indian Cities? How does this ideology affect modern city design? And how is city design related to traditional City design of related province? These questions have led the author to undertake this study. Urban planning and Designing into towns is the beginning of the difficulties of cities’ futures. Whether the main problem is the way of designing and planning or the policy of increasing the population, what New Towns today mainly suffer is the lack of identity and the differentiation between other cities.“For Indian cities, need of multiple models for well-functioning cities with some common ingredients, including a commitment to equality of opportunity, smart designs for upcoming cities, improved housing facilities, smart designs for upcoming cities and a drive to improve the quality of life for habitants has been felt in the twenty first century.”Sultanpur Lodhi with its legacy to have historic palaces, vital landscape, relics from various architectural styles offers a possibility to explore city module for reviving of historical cities. It was found that 81 percent of the urban population in city lived in overcrowded and substandard houses (Office of Punjab urban planning and development authority, 2017). Therefore this is one amongst the top three most densely populated cities in Punjab, India. Its culture combines Hindu, Buddhist, Islamic, Sikh and British influences. As the economy of this city is based on Agro based industries like Rice Sheller and other small scale industries and subsequent housing demand, there is need to protect vibrant culture and impressions. A fine tunings between available local resources and Contemporary urban design practice need to be explored. The study of Sultanpur Lodhi attempts to give reviving a historical and coherent summary of fragmented information about Punjab’s urban design practice.